Лучшие рефераты по всемирной истории - Зинченко Э. Л. (Банк рефератов, 2001)
Экземпляры: СЭ (20030205) / Инвентарный номер: 1047859 / Цена: 43.00 / Сис.шифр: 63.3(0) / Авт.знак: Л 87 / ГРНТИ: 03 / ББК: 63.3(0)я7